Theoretical And Practical Issues of Technical Terminology - Abdullayeva Fotima (Zien Journals, 2022)
This article deals with some general theoretical and practical issues of terminology, including the definition of a term, which word groups to consider as a term, the debate over whether to consider a professional lexical unit as a term, the general state of existing terminological dictionaries, current shortcomings and confusion in terminology, English The specifics of the translation of technical literature, the development of technical terminology of the Uzbek language at the expense of internal resources, including the use of internal terminology of the Uzbek language in the direct translation of English technical terms into Uzbek or the creation of alternative Uzbek terms were critically analyzed and covered.
Keywords: theoretical and practical issues; term; terminology